1D magnetic nitrogen doped carbon-based fibers derived from NiFe Prussian blue analogues embedded polyacrylonitrile via electrospinning with tunable microwave absorption. (1st November 2021) - Chen, Fu; Zhang, Shanshan; Guo, Rundong; Ma, Beibei; Xiong, Yao; Luo, Hui; Cheng, Yongzhi; Wang, Xian; Gong, Rongzhou
Abstract: Exploring excellent microwave absorbing materials (MAMs) to manage the electromagnetic (EM) radiation and interference is still a grand challenge nowadays. In this work, NiFe Prussian blue analogues (NiFe-PBA) embedded in polyacrylonitrile (PAN) fibers is prepared by electrospinning, and the derived NiFe nanoparticles embedded in nitrogen doped carbon fibers (NiFe@NCFs) were synthesized followed a heat treatment process. Among the samples, the minimum reflection loss is −39.7 dB at 11.5 GHz with a small thickness of 2 mm and the broadest effective absorption bandwidth (EAB) is 4.6 GHz with a small thickness of only 1.45 mm. The excellent microwave absorption is attribute to the synergistic effect of suitable impedance matching and intrinsic strong attenuation capability. The quantity of NiFe-PBA embedded in PAN fiber-like precursors could effectively regulate the EM parameters of NiFe@NCFs by adjusting the conductivity and magnetic properties. It is believed that this work would opened up a way for designing novel light-weight, ultrathin-thickness, broadband, strong microwave attenuation capability of magnetic carbon-based MAMs.